Analisis Perencanaan Saluran Drainase Sebagai Upaya Pengendalian Genangan Banjir di Kawasan JL. Adityawarman, Surabaya - Saka, Candra Diri; Wulandari, Esti; Safitri, Dika Ayu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The recurring flooding problem in the Jl. Adityawarman area, Wonokromo District, Surabaya City, is caused by the existing drainage channels no longer being capable of accommodating stormwater runoff discharge. This study aims to analyze the design discharge of the drainage channels and evaluate the capacity of the existing drainage system in the area. The research employed a quantitative descriptive method through hydrological and hydraulic analyses. Maximum daily rainfall data for the 2016–2025 period from the two nearest rainfall stations were analyzed using the Thiessen Polygon method, Log Pearson Type III distribution, and the Rational method. The analysis results indicate design discharges of 5.244 m³/s for a 2-year return period, 6.619 m³/s for a 5-year return period, and 7.602 m³/s for a 10-year return period. The evaluation of the existing channel capacity showed that all 33 channel segments experienced overflow under all return periods, with capacities ranging from 0.36 to 4.92 m³/s. Therefore, an increase in the drainage system capacity in the Jl. Adityawarman area is required.